Feminist Criminology: An Emergence of New Branch: Exploring the Impact and Progress of Feminist Criminology (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The advancement of feminism in criminology and its possibilities are discussed in this article.The emphasis is on feminist and thinking regarding female offenders, victims, and employees in thecriminal justice system during the previous 25 years. A brief outline of the direction of this research isoffered, as well as important conflicts between mainstream and feminist viewpoints. The article alsoconsiders feminist activists' contributions to tangible social change for female victims and offenders, bothinside and beyond the profession. The paper concludes with a consideration of current feministcriminology developments. The basic categories and domains of mainstream criminology are beingchallenged and subverted by thinking concerning women's experiences with crime.Theories on how a crime was committed should ideally begin with an open mind about the perpetrators,the weapon(s), the nature of the crime, and the criminal's purpose. Until the evidence eliminates thesuspect, everybody associated to the scene of the crime or possibly a suspect must be evaluated.Suspects arise as a result of this process of elimination, and they may be probed further until they arecharged.